2018
DOI: 10.2147/jpr.s168705
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive brain stimulation in chronic orofacial pain: a systematic review

Abstract: BackgroundTranscranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are non-invasive brain stimulation techniques that are being explored as therapeutic alternatives for the management of various chronic pain conditions.ObjectiveThe primary objective of this systematic review is to assess the efficacy of TMS and tDCS in reducing clinical pain intensity in chronic orofacial pain (OFP) disorders. The secondary objectives are to describe adverse effects, duration of relief, and TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 67 publications
1
17
0
1
Order By: Relevance
“…Thus, our study is the first to evaluate these interventions. Our results (significant reduction of pain) are consistent with previous literature on tDCS and rTMS effects on other chronic pain 48 and neuropathic pain conditions 46 , also the parameters used in our included studies are similar to previous studies, using motor cortex as the main target region with excitatory stimulation polarity 46 . But our results show a moderate to big effect compared with the small effects reported in other chronic pain conditions 46 .…”
Section: Summary Of Resultssupporting
confidence: 92%
“…Thus, our study is the first to evaluate these interventions. Our results (significant reduction of pain) are consistent with previous literature on tDCS and rTMS effects on other chronic pain 48 and neuropathic pain conditions 46 , also the parameters used in our included studies are similar to previous studies, using motor cortex as the main target region with excitatory stimulation polarity 46 . But our results show a moderate to big effect compared with the small effects reported in other chronic pain conditions 46 .…”
Section: Summary Of Resultssupporting
confidence: 92%
“…M1-cortical excitability alterations have been associated with the severity of the clinical symptoms such as pain intensity, hyperalgesia, and allodynia [9,10], pointing to the value of TMS as an objective tool that reflects functional alterations. Moreover, cortical excitability restoration through repetitive TMS (rTMS), a technique known to induce lasting modulation effects on brain activity through a multiple day session paradigm, has shown some efficacy in reducing the magnitude of pain, even in refractory chronic pain patients [11][12][13][14][15][16]. Overall, these results support the role of cortical excitability on pain intensity in chronic pain patients and the potential clinical utility of TMS in pain management among this population.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, it is known that a higher number of rTMS sessions usually yield larger analgesic effects ( 11 , 13 , 91 , 92 ). Yet, one and two sessions involving similar rTMS protocols than the one used in the present study have been found to increase pain thresholds in healthy volunteers ( 25 ).…”
Section: Discussionmentioning
confidence: 99%